Increased Prevalence Of Stroke Recurrence And Stroke Related Mortality In Children With Sickle Cell Disease In Nigeria: Evidence For A Secondary Stroke Prevention Trial. - Abdullahi, Shehu U. (Pediatr Neurol, 2019)
BACKGROUND-: To improve the quality of care for children with sickle cell anemia (SCA) in Kano, Nigeria, we initiated a standard care protocol in 2014 to manage children with strokes at Aminu Kano Teaching Hospital. METHOD-: The standard care protocol requires that children presenting with acute strokes be treated with hydroxyurea at a fixed dose of 20 mg/kg/day within 2 months of the stroke. RESULTS-: We identified 29 children with SCA who had an initial stroke within the study period, followed for a mean of 1.25 years (to either end of follow up or a second stroke) and corresponding to an initial stroke incidence rate of 0.88 per 100 patient-years. Six children had stroke recurrence while on hydroxyurea, with a stroke recurrence rate of 17.4 events per 100 patient-years, and one child died. None of the children treated with hydroxyurea had therapy held because of myelosuppression; although, adherence was approximately 60%, in part because families had to pay for hydroxyurea. Most likely, we underestimated the incidence of strokes because despite formal training for stroke detection during the quality improvement period, no participant had formal assessment using the pediatric stroke scale. CONCLUSION-: Our results provide strong evidence for the high prevalence of initial strokes in children with SCA in a low-resource setting, requirement for ongoing training to detect strokes with an objective stroke assessment, and the need for government support free access to hydroxyurea.